Neurocognitive functioning in adults with congenital heart disease. (13th December 2016) - Ilardi, Dawn; Ono, Kim E.; McCartney, Rebecca; Book, Wendy; Stringer, Anthony Y.
Abstract: Objective: Adults with congenital heart disease (CHD) are at increased risk of psychological disorders and cognitive deficiencies due to structural/acquired neurological abnormalities and neurodevelopmental disorders as children. However, limited information is known about the neuropsychological functioning of adults with CHD. This study screened neuropsychological abilities and explored group differences related to cardiac disease severity and neurological risk factors in adults with CHD. Design: Participants completed brief neuropsychological testing. Information about neurobehavioral and psychological symptoms, employment, education, and disability were also collected from the patient and a family member. Results: Forty‐eight participants with adult CHD completed neuropsychological testing. Visuospatial skills and working memory were worse than expected compared to the typical population. Frequency of neurological comorbidities (e.g., stroke, seizures) was higher in those with more severe heart disease (e.g., single ventricle or cyanotic disease), and executive functioning was weaker in those with neurological comorbidities. Those with more severe heart disease were more likely to be unemployed and to receive disability benefits, but educational attainment did not differ. Those who received disability performed worse on tasks of executive functioning. Conclusions: Findings suggest concerns about neuropsychological functioning that need to be more comprehensively assessed in adults with CHD. Understanding the cognitive limitations of this aging population can help guide access to resources, transition of care, and medical care engagement, thus improving quality of care and quality of life.